Provenance analysis of the Mesozoic Hoh‐Xil‐Songpan‐Ganzi turbidites in northern Tibet: Implications for the tectonic evolution of the eastern Paleo‐Tethys Ocean. Issue 1 (22nd February 2013) - Ding, L.; Yang, D.; Cai, F. L.; Pullen, A.; Kapp, P.; Gehrels, G. E.; Zhang, L. Y.; Zhang, Q. H.; Lai, Q. Z.; Yue, Y. H.; Shi, R. D.
Abstract : [1] Mesozoic strata of the Hoh‐Xil‐Songpan‐Ganzi complex in northern Tibet are exposed in a vast (> 370, 000 km 2 ) triangle‐shaped orogenic belt bound by the Longmen Shan thrust belt in the east, the Kunlun terrane and North China block in the north, and the Qiangtang terrane and Yidun arc in the south. These strata consist of Middle–Upper Triassic submarine fan and deep marine facies rocks that were deposited in the Paleo‐Tethys Ocean. Late Triassic–Early Jurassic contractional deformation in the eastern Hoh‐Xil‐Songpan‐Ganzi complex marks the demise of the Paleo‐Tethys Ocean basin and the accretion of the Gondwana‐derived Qiangtang terrane to Eurasia. We conducted geological mapping, regional stratigraphic analyses, and U‐Pb geochronology of detrital zircons ( n = 4128) on the Mesozoic sequences exposed in the Hoh‐Xil‐Songpan‐Ganzi complex, Kunlun terrane, and Qiangtang terrane. We identify for the first time marine silciclastic sandstone and shale of Jurassic age in the northwestern Hoh‐Xil‐Songpan‐Ganzi complex that unconformably overlie Upper Triassic turbidites. Zircon age data indicate that the Middle–Upper Triassic marine gravity‐flow deposits of the Hoh‐Xil‐Songpan‐Ganzi complex were shed from the North and South China blocks, and Middle–Late Triassic ultrahigh‐pressure Qinling–Dabie orogenic belt, as well as the Kunlun and Qiangtang terranes. In addition, the detrital zircon results suggest vast sediment source to sink distances (>1500 km) for the Middle–Upper Triassic Hoh‐Xil‐Songpan‐Ganzi strata, which is consistent with tectonic models for the Paleo‐Tethys Ocean basin that incorporate significant components of horizontal tectonic transport like opening of large back‐arc basins in response to oceanic slab rollback. Key Points: The first detailed geochronology, stratigraphic, paleocurrent studies in Hoh‐Xil Identified, for the first time, marine strata of Jurassic age in Hoh‐Xil A submarine channel may have transported sediment from the CAOP to HXSG basin